A real-world study of the tolerability and dosing of pirfenidone and its effect on survival in idiopathic pulmonary fibrosis: Pirfenidone dose and survival in IPF - Dhooria, Sahajal; Agarwal, Ritesh; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Muthu, Valliappan; Garg, Mandeep; Bal, Amanjit; Aggarwal, Ashutosh Nath; Behera, Digambar (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
ackground: Patients with idiopathic pulmonary fibrosis (IPF) often do not tolerate pirfenidone in the recommended dose of 2400 mg/day. The proportion of patients requiring dose reduction and its impact on survival in the real-world remain unclear. Methods: Consecutive subjects with IPF were enrolled between March 2017 and June 2019. The maximum tolerated dose of pirfenidone (primary outcome) and adverse drug reactions (ADRs) were recorded. A post hoc logistic regression analysis was performed to evaluate the predictors of drug discontinuation due to ADRs. We also compared survival between the full-dose (2400 mg/day), reduced-dose (< 2400 mg/day), and the no-pirfenidone groups, with age and percentage of the predicted forced vital capacity (%pred FVC) as covariates. Results: Of the 128 subjects (mean age, 67.4 years; 77.3% men) included, 115 were initiated on pirfenidone. Forty-nine (42.6%) and 51 (44.3%) subjects tolerated the full dose and reduced doses, respectively. Ninety-six (83.5%) subjects developed at least one ADR; anorexia dyspepsia, and nausea being the most common. Twenty-two subjects discontinued the drug; 15 of them due to ADRs. Body mass index < 20 kg/m2 was the only predictor of drug discontinuation due to ADRs. Among subjects newly initiated on treatment during the study period (n = 80), survival was longer (hazard ratio [interquartile range], 0.19 [0.04-0.96]; p = 0.045) in the full-dose but not the reduced-dose group (p = 0.08) compared with the no-pirfenidone group, after adjusting for covariates. Conclusion: Pirfenidone was tolerated in the full dose in a minority of patients with IPF and appears to improve survival only with the full dose.